Optimizing Supply Chains: A Grey-DEMATEL Approach to Implementing LARG Framework - Hossein Talebzadeh; Amirmohammad Fattahiamin; Mohammad Talebzadeh; Fariba Sanaei; Parisa Khorashadi Moghaddam; Shervin Espahbod (Tehnički Glasnik)
The performance of supply chains is directly impacted by overarching strategies and management paradigms. Success in the contemporary business landscape necessitates a comprehensive perspective that caters to the diverse needs of the market. The LARG (Lean-Agile-Resilient-Green) paradigm stands out as a versatile solution capable of addressing various concerns within the supply chain. This study introduces an innovative integrated framework for the implementation of the LARG supply chain, drawing upon insights from literature and expert knowledge, and encompassing 14 key factors. Subsequently, employing the grey-DEMATEL (decision-making trial and evaluation laboratory) method, we quantitatively measure the interrelations among these factors, culminating in the development of a structural model. The research findings underscore the significance of a technological approach as the most impactful factor in facilitating the LARG paradigm within the supply chain.